Probability and desirability of future developments – Results of a large-scale Argumentative Delphi in support of Horizon Europe preparation. (April 2022) - Cuhls, Kerstin; Dragomir, Bianca; Gheorghiu, Radu; Rosa, Aaron; Curaj, Adrian
Abstract: This contribution explores the use of a Foresight tool, namely the Dynamic Argumentative Delphi (DAD) survey, in informing policy-making during the design phase of a new Framework Programme in research, technology, development and innovation (RTDI). The Dynamic Argumentative Delphi enables not only quantitative assessments for future statements, but also supports these estimates with qualitative arguments that are visible to fellow contributors; and ranked in real-time according to the frequency of their selection. Using project "BOHEMIA – Beyond the Horizon" project as an example for a procedure bringing in issues under uncertainty into a policy-making process, we undergo a structural analysis of the content generated (the results of the Delphi survey), exploring the quantitative and qualitative results obtained. More specifically, analysing the argumentation generated by respondents, this paper investigates to what extent the perceived feasibility of statements is consistent with the estimated time of realization and whether the perceived desirability of the statements creates a bias in the estimated time of realization. We observe that participants' argumentation is consistently correlated with the quantitative estimations, where more extended debates on some statements reflect a real dispersion of opinions. Moreover, expressed feasibility is correlated with average time of realization. One rather surprising, but encouraging finding, is the absence of a consistent desirability bias, i.e. more votes for arguments that deem the statement desirable are not correlated with a shorter estimated time of realization. Highlights: New Foresight tool, the Dynamic Argumentative Delphi (DAD) survey explored. Outcomes of the DAD survey in the project "BOHEMIA – Beyond the Horizon" for the preparation of Horizon Europe. Test whether perceived desirability and probability of potential future developments influence the identification and formulation of future issues. Participants' argumentation is consistently correlated with the quantitative estimations, where more extended debates on some statements reflect a real dispersion of opinions. A consistent desirability bias in the answers is not observed.